Role of Mo in catalysts based on noble metals in hydrodeoxygenation reactions - Ballesteros-Plata, Daniel; Infantes-Molina, Antonia; Rodríguez-Aguado, Elena; Braos-García, María del Pilar; Rodríguez-Castellón, Enrique (My University, 2017)
The use of bio-energy as a renewable alternative to fossil fuels is nowadays attracting more and more attention. The bio-fuel from biomass seems to be a potential energy substitute for fossil fuels since it is a renewable resource that could contribute to sustainable development and global environmental preservation and it appears to have significant economic potential1. The problem is its high oxygen content, which gives undesirable properties for combustion. To remove oxygen, catalytic hydrodeoxygenation (HDO) reactions are carried out. Monometallic Mo/Si, Pt/Si as well as bimetallic PtMo/Si catalysts were prepared and evaluated in the hydrodeoxygenation (HDO)reaction of dibenzofurane (DBF) as a model molecule in biomass derived bio-oil.
Keywords: Recursos energéticos renovables; Energía de biomasa